The right parietal lobe, sense of self, and empathy: cross-cultural, ethnic, and religious considerations. Issue 5 (27th May 2020) - Cohen, Daniel; Bhushan, Braj; Hanks, Robin; Yoon, Dong Pil; Johnstone, Brick; Hunt, Issac
ABSTRACT: This study extends previous research where empathy associated with increased right parietal lobe (RPL) "self-orientation" and left hemisphere (LH) "other-orientation" by investigating different cultural (India, US), ethnic (African American, Caucasian, South Asian), and religious (Christian, Hindu, Muslim) groupings. Participants included 108 individuals with traumatic brain injury (TBI) and explored correlations between empathy and neuropsychological measures. Measures included neuropsychological indices of cerebral functional integrity (RPL, left frontal, left temporal) and self-report measures of affective and cognitive empathy. Pearson correlations showed increased RPL functioning positively and significantly associated with increased cognitive empathy for total, India, US, Christian, Muslim, African American, and South Asian samples. LH indices associated positively with both affective and cognitive empathy for US, Caucasian, and Christian participants. Contrary to hypotheses, indices of RPL functioning significantly but negatively associated with affective empathy for Indian, Muslim, and South Asian samples, possibly reflecting different conceptualisations of "self" in individualistic versus collectivist societies.